One Step Histological Detection and Staining of the PTEN Tumor Suppressor Protein by a Single Strand DNA - Gloria Longinotti; Gabriel Ybarra; Susana Vighi; Claudia Perandones; Javier Montserrat; Juan Sebastian Yakisich; Mariano Grasselli; Martin Radrizzani (Diagnostics, 2021)
Antibodies are the most used technological tool in histochemistry. However, even with monoclonal antibodies, their standardization is difficult due to variation of biological systems as well as to variability due to the affinity and amplification of the signal arising from secondary peroxidase detection systems. In this article we combined two synthetic molecules to facilitate the standardization of a detection protocol of protein markers in histological sections. The first molecule was an aptamer, a 50-base single-stranded DNA fragment, which recognizes a PTEN tumor suppressor. The second molecule used was also another single stranded 18-base aptamer DNA fragment, which forms a quadruplex structure guanine box. This G-quadruplex recognizes and attaches a molecule of hemin, increasing the catalytic capacity for the hydrogen peroxide. Our results show how the correct structural design of DNA combining an aptamer together with the peroxidase-like DNAzyme allows to detect proteins in histological sections. This tool offers the standardization of the detection of prognostic markers in cancer, in quality and quantity, due to its synthetic nature and its 1:1 antigen:enzyme ratio. This is the first time that reproducible results have been presented in histological sections staining a cancer marker using a single-stranded DNA molecule with dual function.